Dari Yesus Pembebas Hingga Kristus Kurban - Istata Raharjo, Stepanus (Jurnal Orientasi Baru, 2015)
This article focused on Contextually Christology reflections. They are Leonardo Boff’s Christology reflection in Latin America, Aloysius Pieris’ in Asian, and Banawiratma’s in Indonesian as the examples of Contextual Christology reflection with different context. Comparative method is used to learn the idiosyncrasy of each author in context to present the meaning of Jesus Christ in the church’s struggle and experiences in different context. From this research it was found that contextually Christological reflection found an image of Christ in which it lives and edifying the church struggle now a days. Christians are the majority group in Latin America. The faiths of Jesus Christ encourage fighting for liberation and justice in the middle of various socio economic and politic life of bondage. In Asia, Christian are minority, the preaching of the faith of Jesus Christ as a savior is only effective in a dialogue with a view to safety in Asian religion. In Indonesian contextual, the dialogue with the local community in introducing Christ to be approached by understanding the meaning of sacrifice in relation with a real love of the neighbor.